DIY nutrient film technique (NFT) aquaponic system - Jasni, Nur Aziemah; Said, Rozlianah; Jabridin, Jasmira; Marcus, Forney Felix; Hassan, Mohammad Haiqal (2022)
Malaysia's total population in the year 2021 was 33.45 million, and the need for food production is elevated to feed the nation's mouth. However, Malaysia is currently faced with land scarcity for the agricultural sector and food insecurity. Malaysian agriculture sector competes with other sectors for land, such as industrialization and housing projects. This situation might affect food production for human consumption and contribute to an undernourished issue. Malaysia's land scarcity issues lead to low food production, creating food insecurity and undernourishment. In addition, the COVID-19 pandemic left a tremendous impact on the lower-income group, especially in their food bills. Therefore, aquaponics' soil-less culture technology is a right-thinking way to mitigate listed issues. Plants and fish grow together in one system without soil and less water, limited use of space, source of side income, and produce fresh food from the farm to your table. This study focuses on soil-less agriculture, which is the aquaponic system. This project aims to set up a DIY NFT Aquaponic system and identify the growth of fish and vegetables in different aquaponic treatments. The project was conducted at Unit Ladang, UiTM Sabah Branch, from 10 December 2021 until 28 January 2022. This project uses Tilapia fish and mustard to complete one unit of an aquaponic system. The results show treatments 2 and 3 have decent plant growth and fish development compared to treatment 1. In conclusion, aquaponics can alleviate land scarcity, food insecurity and poverty as it can produce fresh food plus generate income.